Bacterial contamination test on plates, spoons, and glass at a food stall (angkringan) Surakarta City, Central Java - Dara Akwila; Aji Tri Aminougroho; Didik Wahyudi (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
Cutlery is an important component that can affect the health of the digestive tract. Plates, glasses and spoons are eating utensils that are often used by the community. In the city of Surakarta, Central Java, there are many roadside food stalls that are in great demand by the community, namely Angkringan. The purpose of this study was to determine bacterial contamination of cutlery (pring, glass and spoon) at a food stall (Angkringan) in Surakarta City, Central Java. This research is a descriptive observational study, bacteriological examination of cutlery begins with swab sampling, bacterial examination using the Total Plate Number method, and confirmed by Gram staining. The results of the examination of the number of bacterial colonies were compared with the standard reference of Permenkes No. 1096/MENKES/PER/VI/2011, which is 0 colonies/cm2. The results showed the average bacterial contamination in angkringan food stalls in Surakarta City, as follows: plate 10230 colonies/cm2, glass 9560 colonies/cm2 and spoon 3960 colonies/cm2 . All cutlery that was inspected did not meet the standards of Permenkes No. 1096/MENKES/PER/VI/2011.